Optimized Wideband Impedance Matching Balun for Conducting Two-Arm Antennas - Khalid F. A. Hussein (International Journal of Antennas and Propagation)
A split coaxial balun with a step transition of the inner conductor diameter is introduced to satisfy impedance matching between unbalanced feeder and balanced antennas. The location of the step transition along the axis of the balun and the diameter change are two dimensional parameters that are not present in the conventional split coaxial balun. These additional parameters, together with the double slot width, provide more flexibility to design the balun for better impedance matching. The effects of the three dimensional parameters on the input impedance seen at the (unbalanced) coaxial line side of the balun are investigated when it is terminated with specific lumped impedance at its (balanced) split side. An optimization procedure is introduced to arrive at the balun dimensional parameters to give the best matching with specific load impedance. The proposed balun is designed to feed (balanced) two-arm antennas such as the dipole and the bowtie antenna from 50 Ω-coaxial line. The electromagnetic simulation shows that the proposed balun results in a perfect impedance matching. A comparison with the performance of the conventional split balun used to feed a dipole antenna shows that the balun proposed in the present paper gives a much lower value of the return loss at the design frequency and a wider bandwidth for VSWR ≤ 1.5. The simulation results obtained using the MoM are compared with experimental measurements showing good agreement.